2005
DOI: 10.1007/s00428-004-1180-4
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis: humoral and cellular factors of inflammation

Abstract: In the past decade, atherosclerosis has come to be recognized as active and inflammatory rather than simply a passive process of lipid infiltration or a reparative process after endothelial injury. In general, atherosclerosis can be considered as an intramural chronic inflammation resulting from interactions between modified lipoproteins, monocyte-derived macrophages, lymphocytes, and the normal cellular elements of the arterial wall. The process of inflammation occurs in response to functional and structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…In addition, lipocortin 1 (or annexin 1), as mentioned above for macrophages, is also produced by granulocytes (54). Finally, granulocytes are associated with capillary closure in spontaneously diabetic monkey retinas (55), and granulocytes might play a role in atherosclerosis (56).…”
Section: Fig 1 Islet Fibrosis Progresses Rapidly In Mild Hyperglycementioning
confidence: 99%
“…In addition, lipocortin 1 (or annexin 1), as mentioned above for macrophages, is also produced by granulocytes (54). Finally, granulocytes are associated with capillary closure in spontaneously diabetic monkey retinas (55), and granulocytes might play a role in atherosclerosis (56).…”
Section: Fig 1 Islet Fibrosis Progresses Rapidly In Mild Hyperglycementioning
confidence: 99%
“…For instance, autopsies of Egyptian mummies found atherosclerotic plaques in a majority of this sample (16͞24) (15,16). As early as 1858, Virchow concluded that ''an inflammation of the arterial coat was the starting point of the so-called atheromatous degeneration'' (17).…”
mentioning
confidence: 99%
“…11 VV are generally not present in wild-type mice and they do not develop advanced atherosclerotic lesions, but apolipoprotein E (apoE) Ϫ/Ϫ /low-density lipoprotein (LDL) Ϫ/Ϫ double knockout mice develop lesions with considerable structural similarity to human atherosclerosis. 12 The present study was designed to characterize atherosclerotic lesions and the localization and time course of VV neovascularization and adventitial inflammation relative to growing plaques in apoE Ϫ/Ϫ / LDL Ϫ/Ϫ double knockout mice.…”
mentioning
confidence: 99%